The effect of encapsulants on the heat of sorption in vacuum-dried caja powder - Silva Oliveira Gomes, Maron Stanley; Polachini, Tiago Carregari [UNESP]; Lopes Filho, Jose Francisco [UNESP]; Romero, Javier Telis [UNESP] (Univ Federal Ceara, Dept Geol, 2019)
Equilibrium moisture data from the powdered pulp of Spondias mombin, L., both with and without additives - 58% maltodextrin (MD) or 58% gum arabic (GA) - were determined at 20, 30, 40 and 50 degrees C, using the static gravimetric method for a water activity range of 0.06 to 0.90. The resulting isotherms were sigmoidal and typical Type III, with the Guggenheim-Anderson-de-Boer model (GAB) adjusted to the experimental data for equilibrium moisture vs water activity. The addition of additives was shown to affect the isotherms in such a way that, for the same water activity, samples of CP+GA and CP+MD showed a lower equilibrium moisture content and were not affected by the variations in temperature. The isosteric heat of sorption for the caja powder with additives was greater (less negative) than that of the caja powder with no additives, suggesting that polar sites in the product without the addition of GA or MD are more active. An empirical exponential relationship can describe the dependence of the heat of sorption as a function of the moisture content of the material.
Keywords: Isotherms; Maltodextrin; Gum arabic Water activity